Serotonin controlling feeding and satiety - Voigt, Jörg-Peter; Fink, Heidrun (Elsevier, 2015)
Serotonin has been implicated in the control of satiety for almost four decades. Historically, the insight that the appetite suppressant effect of fenfluramine is linked to serotonin has stimulated interest in and research into the role of this neurotransmitter in satiety. Various rodent models, including transgenic models, have been developed to identify the involved 5-HT receptor subtypes. This approach also required the availability of receptor ligands of different selectivity, and behavioural techniques had to be developed simultaneously which allow differentiating between unspecific pharmacological effects of these ligands and ‘true’ satiation and satiety. Currently, 5-HT1B, 5-HT2C and 5-HT6 receptors have been identified to mediate serotonergic satiety in different ways. The recently approved anti-obesity drug lorcaserin is a 5-HT2C receptor agonist. In brain, both hypothalamic (arcuate nucleus, paraventricular nucleus) and extrahypothalamic sites (parabrachial nucleus, nucleus of the solitary tract) have been identified to mediate the serotonergic control of satiety. Serotonin interacts within the hypothalamus with endogenous orexigenic (Neuropeptide Y/Agouti related protein) and anorectic (α-melanocyte stimulating hormone) peptides. In the nucleus of the solitary tract serotonin integrates peripheral satiety signals. Here, the 5-HT3, but possibly also the 5-HT2C receptor play a role. It has been found that 5-HT acts in concert with such peripheral signals as cholecystokinin and leptin. Despite the recent advances of our knowledge, many of the complex interactions between 5-HT and other satiety factors are not fully understood yet. Further progress in research will also advance the development of new serotonergic anti-obesity drugs.